Stirling engine: from design to application into practice and education - Pham , Van Nganh; Ha , Anh Tung (Journal of Technical Education Science, 2016)
Stirling engine is an external combustion engine which is able to use different fuel sources from traditional forms (coal, oil, firewood, rice husks, etc ...) to renewable energy sources (solar, waste energy, etc ...). This paper focuses on presenting the main features of development history, performance characteristics, design methods of typical types of Stirling engine and the possibility of their applications into practice as well as into the current university curriculum for thermal engineering students in Vietnam.